i-Cons 2.0 (Islamic Contracts 2.0) - Punding, Azlan Yusof; Mejri, Norazimah; Suharto, Charolyna; Yusop, Mohamad Khairulamirin; Hussein, Nur Syafiqah (2025)
Islamic banking is increasingly gaining attention due to its compliance with Shariah and Sunnah principles. Governed by the Islamic Financial Services Act 2013, it operates based on ethical and interest-free financial practices. Despite its growth, public awareness and understanding of Islamic banking particularly its concepts and specialized terms remain low. Many people, including students pursuing studies in Islamic finance, often find the subject complex and challenging to grasp. In response to this issue, we have developed an innovative educational tool designed to make learning Islamic banking more accessible and engaging. The innovation developed using wordwall, a free online classroom’s activities include quizzes, matching exercises, word games, and more. This innovation focuses on simplifying the definitions and terminology of Islamic banking, with a special emphasis on Islamic contracts. Known as i-Cons 2.0, these contracts are introduced through interactive and entertaining methods that cater to the learning preferences of 21st-century students. By integrating technology and gamification, our product helps users understand fundamental concepts in a more enjoyable and less intimidating way. The aim is to enhance comprehension while also increasing interest and motivation among learners. Ultimately, our goal is to support students and the wider community in gaining a better understanding of Islamic banking and finance. By making complex ideas more relatable through digital tools and engaging content, we hope to bridge the knowledge gap and encourage more individuals to explore the field. This product not only serves educational purposes but also promotes greater financial literacy rooted in Islamic values.